Intra‐operative fluorescence angiography is reproducible and reduces the rate of anastomotic leak after colorectal resection for cancer: a prospective case‐matched study. (18th May 2020) - Wojcik, M.; Doussot, A.; Manfredelli, S.; Duclos, C.; Paquette, B.; Turco, C.; Heyd, B.; Lakkis, Z.
Abstract: Aim: Intra‐operative fluorescence angiography (IOFA) with indocyanine green provides information on tissue perfusion that may help prevent an anastomotic leak (AL). The aim of this study was to assess the impact of IOFA on outcomes after left‐sided colonic or low anterior resection with anastomosis for colorectal cancer. Methods: All patients with left‐sided colonic or rectal cancer, operated between June 2017 and December 2018, were prospectively included. IOFA has been routinely implemented since May 2018. Reproducibility of IOFA, after a 1:1 matching for relevant clinical risk factors of AL, was studied in patients with IOFA (IOFA+) and without IOFA (IOFA−). Outcomes were compared in terms of postoperative events such as clinically relevant AL as the primary end‐point. Results: In the IOFA+ group, changing of the initially planned colon transection due to inadequate perfusion occurred in five out of 46 patients (10.9%). Agreement between intra‐operative assessment and postoperative blind review of IOFA was deemed strong (Cohen's kappa index 0.893, 95% CI 0.788–0.998, P  < 0.001). Among 111 patients, 42 matched patients were included in each group. There was significantly more clinically relevant AL in the IOFA− group compared to the IOFA+ group (16.7% vs 2.4%, P  = 0.026) involving significantly more anastomotic dehiscence which required re‐intervention (19% vs 2.4%, P  = 0.014). Additionally, more descending colon ischaemia/necrosis was observed in the IOFA− group compared with the IOFA+ group (9.5% vs 0%, P  = 0.040). Conclusion: In this prospective case‐matched study, IOFA decreased the occurrence of clinically relevant AL due to necrosis of the descending colon or anastomosis. Upon blind review, perfusion assessment using IOFA was reproducible.